Estratégias de estudo para o solista de orquestra aplicadas na construção da performance do concerto para violão e orquestra de Ricardo Tacuchian - Silva, Fabricio Ferreira da (2018)
This work has as objective to present the planning and strategies of studies applied in the construction of the performance of the concert for acoustic guitar and orchestra by composer Ricardo Tacuchian (1939). This concert for acoustic guitar and orchestra was ordered by the Brazilian guitarist Turibio Santos (1943) to whom the composer dedicated it in 2008. The results of this research were acquire through the following methodologies: the artistic practice of the researcher/interpreter, in which this is in the line of artistic research identified by Zamboni (2001), and López Cano (1966). The works of Chaffin and Pascual-Leone (2001) that are used as theoretical references that help in the construction and development of strategies, to uniting with the researcher's artistic practice. The planning and preparation of the performance for the acoustic guitar and orchestra from Tacuchian was divided in three steps: PREPARATION, REHEARSAL and CONCERT and ASSESSMENT. The tools used for data collection consisted of a daily study, bibliographic research and interviews. As a result of this research was built the performace of the concert for guitar and orchestra of Ricardo Tacuchian.